2017
DOI: 10.1021/acsphotonics.7b00184
|View full text |Cite
|
Sign up to set email alerts
|

Low-Threshold Plasmonic Lasers on a Single-Crystalline Epitaxial Silver Platform at Telecom Wavelength

Abstract: We report on the first demonstration of metal−insulator−semiconductor-type plasmonic lasers at the telecom wavelength (∼1.3 μm) using top-down fabricated semiconductor waveguides on single-crystalline metallic platforms formed using epitaxially grown Ag films. The critical role of the Ag film thickness in sustaining plasmonic lasing at the telecom wavelength is investigated systematically. Low-threshold (0.2 MW/cm 2 ) and continuous-wave operation of plasmonic lasing at cryogenic temperatures can be achieved o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Among those efforts, the concept of diffraction-unlimited plasmonic nanocavity has been proposed. 3,4 This novel type of nanoscale cavity involves surface plasmons localized at the interface between metal and dielectric material. The localized mode conned at the interface is known as surface plasmon polaritons (SPPs) which means strong coupling between surface plasmons and photons.…”
Section: Introductionmentioning
confidence: 99%
“…Among those efforts, the concept of diffraction-unlimited plasmonic nanocavity has been proposed. 3,4 This novel type of nanoscale cavity involves surface plasmons localized at the interface between metal and dielectric material. The localized mode conned at the interface is known as surface plasmon polaritons (SPPs) which means strong coupling between surface plasmons and photons.…”
Section: Introductionmentioning
confidence: 99%
“…Benefited from the diverse semiconductor materials, the lasing spectrum has been extended to UV and NIR that covering the whole VIS region . For example, in 2014, Lu et al demonstrated an all‐color plasmonic nanolasers with ultralow thresholds using In x Ga 1− x N/GaN core–shell nanorods supported on an Al 2 O 3 ‐capped epitaxial Ag film (Figure c) .…”
Section: Experimental Demonstrations Of the Plasmonic Nanolasersmentioning
confidence: 99%
“…The output wavelength of the plasmonic lasers can be easily tuned by the period of metallic nanostructure array as well as the incident angles. Despite the great potentials of plasmonic lasers in nanophotonics, owing to the high Ohmic loss, the threshold of plasmonic lasers is quite high yet and the electrically‐driven plasmonic laser is still challenging so far, strongly hindering their practical applications . Exploring new optical gain materials is necessary to explore the application‐level plasmonic lasers.…”
Section: Surface‐plasmon‐assisted Semiconductor Micro/nanolasermentioning
confidence: 99%